Bridges not walls : (McGraw-Hill Higher Education, 2009)
This anthology offers fifty-one scholarly and popular readings, that examine a broad range of topics about interpersonal relationships, drawing from such disciplines as communication, philosophy, social science, and psychology. The thought-provoking articles discuss the nature of interpersonal contact, connections between verbal and nonverbal cues, person perception, listening, identity management, gender and ethnic similarities and differences, communication about sex, defensiveness, power, bullying, transformational conflict management, cross-cultural communication, and dialogue. This tenth edition features 23 new readings, including a new chapter focused on listening and talking about sex